Control of Echinochloa sp. in the Irrigated Rice Crop - Luís Eduardo Panozzo; Dirceu Agostinetto; Pedro Valério Dutra de Moraes; Deivid Araújo Magano; Adilson Harter; Luciana Barros Pinto (International Journal of Agronomy)
The species of Echinochloa (barnyardgrass) stand out among major weeds infesting rice cropping and damages are variable depending on the weed population, rice cultivar, and management practices adopted by rice farmers. The objective of this work was to measure the control of barnyardgrass in rice cropping, cultivar Qualimax 1, due to the early times of flood irrigation, application times, and doses of penoxsulam. The experiment was conducted in the field, where the experimental design used a randomized block design with a split plot design with four replications. The treatments consisted of two application periods (early and late) of penoxsulam three times of irrigation start (1, 15 and 30 days after treatment application—(DAT)) and herbicide doses (0, 24, 36, 48 and 60 g ha−1). The herbicide penoxsulam revealed that combined with irrigation starting 15 days after herbicide application promoted efficient control of barnyardgrass.